The influence of boundary condition functions on the quality of the solution and its sensitivity to coefficients of k-ε turbulence models - Ewa Błazik-Borowa (Budownictwo i Architektura, 2011)
The paper is devoted to the problem of boundary conditions influence on the quality of the solution obtained with use of k-ε turbulence models. There are calculation results for different boundary conditions and two methods: standard k-ε and RNG k-ε in the paper. The flow parameters obtained from the calculation are compared with our own measurement results. Moreover, the influence of input data on the inflow edge on sensitivity coefficients is shown and analysed in the paper. The research is performed for components of velocity and turbulence kinetic energy.